Diseño y construcción de un compresor de oxígeno como complemento alternativo del sistema de generación y distribución de oxígeno del Hospital Manuel Y. Monteros del Instituto Ecuatoriano de Seguridad (IESS) de Loja. - Cabrera Sarmiento, Julio César (2009)
The present thesis project understands "The design and construction of an oxygen compressor like alternative complement of the generation system and distribution of oxygen of the Hospital Manuel Y. Monteros of the Ecuadorian Institute of Social security (IESS) of Loja." Having as specific objectives: "To determine an appropriate system and insurance for the process of oxygen compression, the design of a team compressor like complement of the system of oxygen extraction PSA characteristic of the hospital and their later construction for an appropriate and efficient operation that guarantees a continuous supply to the net of distribution of existent oxygen in this house of health. It is necessary to emphasize the importance of this project, since their application like component of a hospital oxygen net, demand of a good design, based on norms and characteristic of compressors for special processes. In the course of the investigative process it was determined convenient to design an alternative compressor of piston since their application field it allows their use in this type of facilities. Being this compressor the base of the present study.